(3Ts) Green conservation framework: A hierarchical-based sustainability approach. (October 2022) - Shehata, Alaa O.; Megahed, Naglaa A.; Shahda, Merhan M.; Hassan, Asmaa M.
Abstract: Conservation of heritage buildings presents a significant approach to cultural identity and continuity. In this regard, previous literature has focused on architectural heritage. However, limited studies have been conducted to investigate the sustainable conservation hierarchy. Given the potential integration of Sustainable Development Goal requirements and green conservation of heritage buildings, this paper develops a hierarchical-based sustainability approach, which refers to the 3Ts green conservation framework. Based on this developed framework, three acronyms, namely, targets and green retrofitting, tools for building information modeling, and tasks through stakeholder involvement, have been proposed. The proposed framework identifies how green sustainable initiatives can be incorporated into heritage buildings, while preserving their significance and characters, through three acronyms, which should be considered simultaneously across the different hierarchical conservation stages, including heritage identification, documentation stage, action plan, and follow-up. Graphical abstract: Image 1 Highlights: An innovative green conservation framework (3Ts) was proposed. The proposed framework emphasized: targets, tools, and tasks. The integration of sustainability and conservation through green retrofitting. BIM application can enhance the sustainable heritage conservation framework. Stakeholders' Involvement is needed to enhance the sustainable retrofit decision.